Molecular Sensing Based on Metal Quantum Wire in Solution - Liu, Junhua; Zhang, Qingyun; Zheng, Pei; Dong*, Xiaodong (Asian Journal of Chemistry, 2014)
Stable gold and silver quantum wires with atomic-scale were successfully fabricated with an electrochemical method in solution and the molecular adsorption onto the quantum wires were studied. The conductance of gold quantum wires showed a decrease upon exposure to definite concentration of dopamine solution and the conductance of silver quantum wires showed an increase upon exposure to ascorbic acid solution. Different sensor mechanisms were proposed with the two kinds mental quantum wire. Because the quantized conductance is determined by a few atoms at the narrowest portion of each quantum wire, adsorption of a molecule onto the portion is enough to change the conductance, which may be used for chemical sensors.